Neurociência e Educação : revisão bibliográfica em teses e dissertações brasileiras - Staudt, Michelli (2020)
This research seeks to analyze how the advances in Neuroscience have been considered in the educational field, with its possibilities and limitations, considering that both exist. In this sense, in order to map the studies developed in Brazil, the following question is defined as the central question of the study: what do the Brazilian researches developed in the field of Neuroscience Education reveal. From it, it is generally sought to present the characteristics of Brazilian production in theses and dissertations in the field of Education that use Neuroscience as a subject of study, in a more specific way, it is intended: to identify the theses and dissertations produced in Brazil and linked to the study theme; talk about conditions Memory, Motivation, Emotions, Attention, Brain Plasticity and Executive Function, associated with Neuroscience; and, analyze how these conditions are present in theses and dissertations. To this end, a study of the “state of knowledge” type was carried out, based on the proposal of Romanowski and Ens (2006), in which the survey and selection occurred through descriptors; in this case, from the CAPES Thesis Bank, in which 10 theses and 28 dissertations were identified. The corpus analysis seeks to elucidate the characteristics of the investigated theses and dissertations, namely: subjects and groups interested in the theme; research context present in the studies; and, presence of the conditions investigated in education research. At the end of the analysis of these 38 works, it was identified that the researches that address conditions: Memory, Motivation, Attention, Emotion, Cerebral Plasticity and Executive Functions linked to Neuroscience and Education have grown in the last three years, although there is still a need to improve the articulation between both areas. There was a need to expand discussions involving especially pedagogical practices that are supported by the results pointed out by neuroscience.